The Interplay of Eclogitization and Deformation During Deep Burial of the Lower Continental Crust—A Case Study From the Bergen Arcs (Western Norway). Issue 3 (7th March 2019) - Zertani, Sascha; Labrousse, Loic; John, Timm; Andersen, Torgeir B.; Tilmann, Frederik
Abstract: The island of Holsnøy in the Bergen Arcs, which belong to the Caledonides of western Norway, represents an excellent example of how fluid‐induced eclogitization modifies material deeply buried by subduction and continental collision. We produced a new detailed map of the northwestern part of Holsnøy, differentiating not only the magnitude of eclogitization but also the strain intensity at different spatial scales: from the outcrop to the entire massif. Using structural data from eclogite‐facies shear zones and eclogitized low‐strain domains, we show that fluid‐mediated eclogitization not only progresses via the development of shear zones (dynamic eclogitization) but occurs over large areas of the island without associated deformation, creating a characteristic static eclogite‐facies overprint. Static eclogitization preserves the structural features of the granulitic protolith while the rock body is transformed from a granulite‐ to an eclogite‐facies mineral assemblage. The extent of static eclogitization was underestimated strongly in the past, a finding also relevant for the interpretation of seismological images in currently active orogens, where presumably similar processes are currently occurring. In addition, we find that the general structure of the eclogite‐facies shear zones is scale‐independent over several orders of magnitude. Although crustal‐scale eclogite‐facies complexes are rarely preserved without significant modification during exhumation, this implies that similar geometrical configurations are likely produced at the scale of the whole lower crust during subduction or continental collision and therefore shape the crustal geophysical signature. Key Points: The fluid‐induced eclogitization on Holsnøy is controlled both dynamically by shear zone development and static equilibration Eclogite‐facies shear zone geometry on Holsnøy is scale‐independent from centimeter to kilometer scale